Considerations for the management of colorectal cancer during the Covid-19 pandemic - Carlos Augusto Rodrigues Véo; Maximiliano Cadamuro; Gilmar Espírito Santo; Rafael Oliveira de Souza; Daniel Cesar; Paulo Henrique de Sousa Fernandes; Reitan Ribeiro; Heber Salvador de Castro Ribeiro; Alexandre Ferreira Oliveira (Brazilian Journal of Oncology)
The number of people infected with the coronavirus (COVID-19) is increasing rapidly in Brazil. It has been proven that COVID-19 can be transmitted from human to human and can lead to hospital-acquired infections, which seriously threaten surgical teams and inpatients. We emphasize that the following suggestions are based on minimal worldwide experience in coping with the disease and are in line with similar attempts to recognize better therapies. Thus, these recommendations can be modified.